A preliminary study on household air pollution exposure and health-related factors among rural housewives in Gansu province, northwest China. Issue 8 (14th September 2022) - Huang, Yushan; Wang, Huiling; Guo, Huizhen; Liu, Yang; Zeng, Yong; Hu, Fengjing; Zhang, Wenwen; Li, Chengyun; Wang, Junling
Abstract: This study monitored the indoor air PAHs and PM2.5 exposure and their seasonal variations, so as to explore the potential health effects of household air pollution (HAP) on rural women's health in northwest China. It was detected that the average indoor PM2.5 and PAHs concentrations in the heating season were both significantly higher than those in the non-heating season ( P <0.01). And they were positively correlated with the urinary 1-OHP levels respectively. Then the PAHs and 1-OHP were both significantly correlated with the urinary 8-OHdG levels ( P <0.05). By statistical models, household PM2.5 and PAHs were closely related to urinary 1-OHP levels. Similarly, PM2.5, PAHs and 1-OHP all have significant effects with urinary 8-OHdG ( P <0.05). Therefore, housewives in rural northwest China were exposed to higher HAP, and it could improve the risk for oxidative damage.